(untitled) - Penelope, Julia; Wolfe, Susan J (Freedom, CA, 1993)
Includes bibliographical references; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Lesbians -- United States -- Literary collections; American literature -- Women authors; American literature -- 20th century; Lesbians' writings, American; Đồng tính nữ -- Hoa Kỳ -- Bộ sưu tập văn học; Văn học Mỹ -- Tác giả nữ